Associations between the burdens of comorbid sleep problems, central sensitization, and headache-related disability in patients with migraine - Suzuki, Keisuke; Suzuki, Shiho; Haruyama, Yasuo; Funakoshi, Kei; Fujita, Hiroaki; Sakuramoto, Hirotaka; Hamaguchi, Mai; Kobashi, Gen; Hirata, Koichi (Frontiers in Neurology, 2024)
Objective Sleep disturbances are common in migraine patients and affect quality of life. Central sensitization (CS) is likely to play a role in the increased severity and chronicity of migraine. We hypothesized that the number of comorbid sleep problems would affect headache-related disability through the effects of central sensitization (CS). Methods We performed a cross-sectional study including 215 consecutive patients with migraine. Insomnia was defined as a Pittsburgh Sleep Quality Index (PSQI) global score greater than 5. Probable REM sleep behavior disorder (pRBD) was defined as an RBD screening score of 5 or greater. Excessive daytime sleepiness (EDS) was defined as an Epworth Sleepiness Scale score of 10 or higher. Suspected sleep apnea (SA) was defined as patients with snoring or sleep apnea witnessed 3 or more nights a week. CS was assessed by the Central Sensitization Inventory (CSI). Results Restless legs syndrome, insomnia, EDS, SA and pRBD were observed in 25.6%, 71.6%, 34.4%, 10.2%, and 21.4%, respectively, of the patients. At least one sleep problem was present in 87.0% of the patients. According to the results of the multinomial logistic regression analysis with no sleep problems as a reference, after we corrected for adjustment factors, the Migraine Disability Assessment (MIDAS) score significantly increased when three or more comorbid sleep problems were present. According to our mediation analysis, an increased number of sleep problems had a direct effect on the MIDAS score after we adjusted for other variables, and the CSI score was indirectly involved in this association. Conclusion The present study showed an association between migraine-related disability and the burden of multiple sleep problems, which was partially mediated by CS.